The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1111/andr.12407
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic role of ADGRG2 in CBAVD patients replicated in Chinese population

Abstract: Congenital bilateral absence of the vas deferens (CBAVD) is an important cause of obstructive azoospermia and male infertility worldwide. Cystic fibrosis transmembrane conductance regulator (CFTR) mutations are the main pathogenic cause, although a proportion of cases are still unexplained. Recently, adhesion G protein-coupled receptor G2 (ADGRG2) gene, a novel pathogenic gene for CBAVD was identified. We did a single population replication study in Chinese CBAVD patients to replicate its role in CBAVD develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 15 publications
1
27
0
2
Order By: Relevance
“…Patat et al identified three hemizygous ADGRG2 variants causing truncated proteins in four patients by whole exome sequencing after excluding CFTR variants. We replicated these findings in a cohort of Chinese CBAVD patients and also detected another two ADGRG2 deleterious missense variants in two CFTR ‐negative patients (Yang et al, ), supporting the fact that ADGRG2 variations may explain a proportion of CBAVD cases.…”
Section: Introductionsupporting
confidence: 81%
“…Patat et al identified three hemizygous ADGRG2 variants causing truncated proteins in four patients by whole exome sequencing after excluding CFTR variants. We replicated these findings in a cohort of Chinese CBAVD patients and also detected another two ADGRG2 deleterious missense variants in two CFTR ‐negative patients (Yang et al, ), supporting the fact that ADGRG2 variations may explain a proportion of CBAVD cases.…”
Section: Introductionsupporting
confidence: 81%
“…The establishment of the causal role of these mutations in the iCBAVD phenotype was based on a set of arguments: (i) male ADGRG2 knockout (KO) mice develop OA without any other significant abnormality (Davies et al 2004), (ii) histological examination of an epididymal biopsy of one of the four individuals showed a lack of expression of ADGRG2 in the epithelium of efferent ductules that were abnormally dilated, (iii) one of the truncated mutations was identified in two infertile individuals related by a maternal link (a nephew and a maternal uncle). Since then, three publications (Yang et al 2017;Yuan et al 2019; Khan et al 2018) have reported the identification of five new rare variations of ADGRG2 in six iCBAVD patients of Asian origin with no pathogenic CFTR mutation: two nonsense mutations classified as pathogenic, including one in two infertile brothers of Pakistani origin (Khan et al 2018) and three missense mutations, including one affecting the GPS region which was classified as pathogenic (Yang et al 2017). These six patients had no renal abnormalities.…”
Section: Adgrg 2 Mutationsmentioning
confidence: 99%
“…A recent study of OA patients with CBAVD and CFTR -negative results reported loss-of-function mutations in ADGRG2 in 3/26 patients (~12%). Another study in a Chinese population identified missense mutations in a small fraction of OA patients, suggesting varied incidence of ADGRG2 mutations in different ethnic groups 17 . While truncating mutations were reported in the gene previously 16 , 17 , here we reported the first Pakistani family with an ADGRG2 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in a Chinese population identified missense mutations in a small fraction of OA patients, suggesting varied incidence of ADGRG2 mutations in different ethnic groups 17 . While truncating mutations were reported in the gene previously 16 , 17 , here we reported the first Pakistani family with an ADGRG2 mutation. This study offers strong evidence with mutation co-segregating with phenotype in 5 affected males and 5 additional family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation